An ethical analysis of UK drug policy as an example of a criminal justice approach to drugs: a commentary on the short film Putting UK Drug Policy into Focus - Adam Holland (BMC, 2020)
Abstract Background Drug-related deaths in the UK are at the highest level on record-the war on drugs has failed. A short film has been produced intended for public and professional audiences featuring academics, representatives of advocacy organisations, police and policymakers outlining the problems with, and highlighting alternative approaches to, UK drug policy. A range of ethical arguments are alluded to, which are distilled here in greater depth for interested viewers and a wider professional and academic readership. Main body The war on drugs is seemingly driven by the idea that the consumption of illegal drugs is immoral. However, the meaning ascribed to 'drug' in the illicit sense encompasses a vast range of substances with different properties that have as much in common with legal drugs as they do with each other. The only property that distinguishes illegal from legal drugs is their legal status, which rather than being based on an assessment of how dangerous they are has been defined by centuries of socio-political idiosyncrasies. The consequences of criminalising people who use drugs often outweigh the risks they face from drug use, and there is not convincing evidence that this prevents wider drug use or drug-related harm. Additionally, punishing someone as a means, to the end of deterring others from drug use, is ethically problematic. Although criminalising the production of harmful drugs may seem more ethically tenable, it has not reduced the supply of drugs and it precludes effective regulation of the market. Other potential policy approaches are highlighted, which would be ethically preferable to existing punitive policy. Conclusion It is not possible to eliminate all drug use and associated harms. The current approach is not only ineffective in preventing drug-related harm but itself directly and indirectly causes incalculable harm to those who use drugs and to wider society. For policymakers to gain the mandate to rationalise drug policy, or to be held accountable if they do not, wider engagement with the electorate is required. It is hoped that this film will encourage at least a few to give pause and reflect on how drug policy might be improved.